The international migration of knowledge workers: when is brain drain beneficial? - Peter Kuhn; Carol McAusland (Institute for the Study of Labor (IZA), 2006)
We consider the welfare effects of the emigration of workers who produce a public good (knowledge). We distinguish between the knowledge diversion and knowledge creation effects of such emigration, and show that the remaining residents of a country can gain from emigration, even when tastes for knowledge goods exhibit a kind of 'home bias'. In contrast to existing models of beneficial brain drain (BBD), our results do not require agglomeration economies, education-related externalities, remittances, return migration, or an emigration lottery. Instead, they are driven purely by the public nature of knowledge goods, combined with differences in market size that induce greater knowledge creation by emigrants abroad than at home. BBD is even more likely in the presence of weak sending-country intellectual property rights (IPRs), or when source country IPR policy is endogenized.
urn:nbn:de:101:1-20080509217
Keywords: 330